The effect of EGFR‐TKIs on survival in advanced non‐small‐cell lung cancer with EGFR mutations: A real‐world study - Xiaoqing Yu; Jinfei Si; Jingwen Wei; Yanling Wang; Yan Sun; Jianan Jin; Xiaoyan Zhang; Tonghui Ma; Zhengbo Song (Cancer Medicine, 2023)
Abstract Background Few large‐scale studies have been published using real‐world data related to overall survival (OS) improvements in advanced epidermal growth factor receptor (EGFR)‐mutant lung cancer patients; therefore, little is known regarding the characteristics of patients who could benefit most from EGFR‐tyrosine kinase inhibitors (TKIs). Our study aimed to assess whether EGFR‐TKI treatment confers survival benefits among advanced non‐small‐cell lung cancer (NSCLC) patients harboring EGFR mutations in the Chinese population. Patients and Methods A total of 6451 advanced NSCLC patients were diagnosed between January 1, 2013 and June 30, 2019 in Zhejiang Cancer Hospital. Ultimately, 2864 patients with a confirmed EGFR mutation genotype were enrolled in our study. OS was measured from the time of diagnosis of advanced NSCLC until death or last follow‐up. Results Median follow‐up for OS of advanced EGFR‐mutant NSCLC patients was 28.33 months in our study. Patients who received EGFR‐TKIs demonstrated better survival compared to those without EGFR‐TKI treatment (mOS: 29.77 vs. 22.97 months, p < 0.0001). A total of 451 patients switched to third‐generation EGFR‐TKI treatment and obtained a significantly better survival than those who adopted first‐line third‐generation EGFR‐TKIs or those who did not receive third‐generation EGFR‐TKIs after disease progression with first‐ or second‐generation EGFR‐TKI treatment (mOS: 38.0 vs. 32.5 vs. 28.3 months, p < 0.0001). As for EGFR genotypes, patients with exon 19 deletion showed better OS, followed by those with L858R mutation (32.4 vs. 24.83 months, p = 0.0013). NGS versus PCR testing showed no statistical differences with respect to survival outcomes (mOS: 27.5 vs. 27.47 months, p = 0.6745). Conclusion Advanced EGFR‐mutant patients treated with EGFR‐TKIs obtained absolute superior survival in the Chinese population.